The complete mitochondrial genomes of three Evacanthini species, Evacanthus bivittatus, Carinata ganga, and Carinata recurvata, and phylogenomic analysis of the Evacanthini - Jiang, Sai; Li, Ran; Jiang, Lina; Wang, Wei; Liu, Yongcheng; Yang, Yuewei; Li, Zizhong (Frontiers in Ecology and Evolution, 2024)
The mitochondrial genome is recognized for its utility in insect molecular research, due to its distinctive features, including fast evolutionary rate, low recombination, and maternal inheritance. In this study, we explored the mitochondrial genome in the context of the leafhopper subfamily Evacanthinae, which is significant in the agricultural pest sector due to the direct and indirect damage caused to plants by its species. We present complete mitochondrial genome sequences for three species: Evacanthus bivittatus, Carinata ganga, and Carinata recurvata. Comparative analyses of nucleotide composition, codon usage of protein coding genes (PCGs), nucleotide diversity, transfer RNA secondary structure, and gene overlap were conducted. To understand phylogenetic relationships among species, we constructed phylogenetic trees using nucleotide sequences from the 13 PCGs of the genomes newly sequenced in this study alongside other available leafhopper genome sequences. Phylogenetic analysis supported monophyly of the Evacanthinae subfamily and suggested a close relationship between the Evacanthini and Nirvanini tribes. Our research indicates that anticodon differences in trnS1 are insufficient to serve as taxonomic markers for distinguishing between these two tribes. This study contributes valuable genetic data supporting ongoing investigations into genetic diversity, molecular evolution, and species identification, while laying groundwork for future taxonomic and evolutionary endeavors within Cicadellidae.